1982
DOI: 10.1289/ehp.824619
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and pharmacokinetics of alternate drinking water disinfectants.

Abstract: The chlorination of surface waters is known to elevate trihalomethanes; consequently, chlorine dioxide (CI02) is being considered as an alternative disinfectant. The primary products resulting from C102 disinfection of waters are chlorites (CIO2-) and chlorates (C103-). Studies in rats revealed that C102 is converted to chloride (ClI), CIO2-and CIO3-. C1O2-and CIO3-are excreted as Cl1, C102-and Cl-, C102-, Cl03-, respectively. Radioactivity was rapidly absorbed from the gastrointestinal tract following the adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
3
5

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 3 publications
4
37
3
5
Order By: Relevance
“…In cattle, the vast majority of urinary radioactivity was chlorate with little chloride and no chlorite being present. The doses of chlorate administered to cattle in this study were much greater than the dose administered to rats (0.15 mg/kg body weight) by Abdel-Rahman et al (15). In addition, their data were collected over a withdrawal period of 72 h after a single administration, whereas data in this study were collected after three doses and only an 8 h withdrawal period.…”
Section: Distribution and Disposition Of Radioactive Residues The Exmentioning
confidence: 78%
See 1 more Smart Citation
“…In cattle, the vast majority of urinary radioactivity was chlorate with little chloride and no chlorite being present. The doses of chlorate administered to cattle in this study were much greater than the dose administered to rats (0.15 mg/kg body weight) by Abdel-Rahman et al (15). In addition, their data were collected over a withdrawal period of 72 h after a single administration, whereas data in this study were collected after three doses and only an 8 h withdrawal period.…”
Section: Distribution and Disposition Of Radioactive Residues The Exmentioning
confidence: 78%
“…Furthermore, the safety of chlorate residues in edible tissues of cattle has not been demonstrated. In rodents, chlorate appears to be rapidly absorbed and excreted (15) and chlorate is apparently metabolized to chlorite and chloride ions. The overall goal of this study was to determine if further development of chlorate as a commercial product was warranted from the perspective of the magnitude of residues in edible tissues.…”
Section: Introductionmentioning
confidence: 99%
“…, 1978; Steffen & Seitz, 1981; Eysseric et al. , 2000), there is scant literature in which any pharmacokinetic parameters were measured (Abdel‐Rahman et al. , 1982, 1985; Steffen & Wetzel, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Ingested chlorite is rapidly absorbed through the gastrointestinal tract and enters the blood stream where it interacts with erythrocytes. Abdel‐Rahman et al () have reported that after ingestion, the highest concentrations of chlorite were found in the blood and stomach. We have used human erythrocytes as an experimental model in our study of chlorite toxicity, especially on the antioxidant system.…”
Section: Resultsmentioning
confidence: 92%
“…When inhaled, dusts or mists of NaClO 2 cause irritation of the mucous membrane and respiratory tract. After ingestion, chlorite is distributed throughout the body with the highest concentrations being found in the blood, stomach, testes, skin, lung, kidneys, small intestine, spleen, brain, bone marrow, and liver (Abdel‐Rahman et al, ). The major adverse health effects of NaClO 2 exposure in humans are methemoglobinemia, severe oxidative hemolysis, disseminated intravascular coagulation, and anuric acute kidney injury (Romanovsky et al, ).…”
Section: Introductionmentioning
confidence: 99%